2016
DOI: 10.1186/s13104-016-1876-y
|View full text |Cite
|
Sign up to set email alerts
|

Insight to changing morphologic patterns of glomerulopathy in adult Pakistani patients: an institutional perspective

Abstract: BackgroundIdiopathic nephrotic syndrome encompasses diverse histogenetic patterns and depicts socioeconomic and demographic differences attributable to genetic profile, environmental factors and prevalence of infectious diseases. A lack of renal registry in our country necessitates a need to document changing histologic patterns of nephrotic syndrome as noted in different parts of the world.MethodsWe retrospectively analyzed 140 patients who underwent renal biopsy at Liaquat National Hospital from January 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…In the present study, primary focal segmental glomerulosclerosis (53.8%) was the most common histological diagnosis. Our findings are also in agreement with multiple local studies 15,16 and international studies 17,18 . As far as we reviewed the literature on FSGS, we noted it as the most prevalent type of histological pattern among Asians of middle age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, primary focal segmental glomerulosclerosis (53.8%) was the most common histological diagnosis. Our findings are also in agreement with multiple local studies 15,16 and international studies 17,18 . As far as we reviewed the literature on FSGS, we noted it as the most prevalent type of histological pattern among Asians of middle age.…”
Section: Discussionsupporting
confidence: 93%
“…al. (27.7%)15 and Hashmi et al (33.6%)16 . Outside Pakistan, it is reported by Hamilton et al in the United Kingdom (11.4%)17 and Hu et al 24.96% in China18 .…”
mentioning
confidence: 91%
“…Glomerular diseases are one of the most important insidious sources of chronic renal failure [1]. Although primary glomerulopathies remain an important cause [2], most of the cases result from secondary etiologies among which diabetes and systemic lupus erythematosis (SLE) are in top of the list. Renal involvement in SLE is sometimes not readily apparent leading to late presentation and poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In our study cohort, we found an increased number of FSGS (30.9%) and membranous glomerulonephritis (23.5%), highlighting the need for further research to find the prevalence of associated variables such as hepatitis B and HIV infections in at-risk populations [ 24 ].…”
Section: Discussionmentioning
confidence: 99%